D.C. Electrical Properties of MgCl2–Filled PEO Films - Salih, A.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The D.C. electrical properties of poly (ethylene oxide)/MgCl2 composites were investigated as a function of different MgCl2 filler concentrations (0, 5, 10, 15 and 20 wt.%) and different temperatures in the range (276â€“333)o K at three different polarizing fields. Resistivity:ï² and dc Conductivity: Ïƒ dc were measured, and the activation energy: Ea of the thermal rate-process of the electrical conduction was investigated. It was found that the current-voltage measurement results exhibited Ohmic resistance behavior, the composites exhibit negative temperature reliance of resistivity and enhancement in the D.C. electrical conductivity with both temperature and MgCl2 concentration. The determined activation energy was found to decrease with both applied polarizing fields and MgCl2 content. The observed overall mechanism of electrical conduction was discussed on the basis of mobility of PEO chains and to the transfer of electrons through the salt aggregations distributed in the polymer matrix, and it was observed that all of the composites were found to be similar to the semiconducting behavior.